Bridging the gap — biomimetic design of bioelectronic interfaces. (December 2021) - Prominski, Aleksander; Tian, Bozhi
Graphical abstract: Highlights: Biomimetic designs can improve the compatibility and efficiency of bioelectronics. Biomimetic designs enable seamless biointegration down to the subcellular and molecular levels. Properties, form, function, and formation mechanism are cornerstones for biomimetic device designs and implementation. Probes resembling neurons and materials assembled through genetic targeting represent new biomimetic design approaches. Abstract : Applied bioelectronic interfaces have an enormous potential for their application in personalized medicine and brain-machine interfaces. While significant progress has been made in the translational applications, there are still concerns about the safety and compliance of artificial devices interacting with cells and tissues. Applying biomimetic design principles enables developing new devices with improved properties in terms of their signal transduction efficiency and biocompatibility. Learning from the paradigms of biological architecture, we can define four cornerstones of biomimetics, which can guide designing new bioelectronic devices or providing improved solutions to challenging biomedical problems. Recent progress shows how these paradigms were successfully employed, for example, to create neuron-like electronics and assemble electronic materials in situ onto the cell membranes using genetic targeting.